Pengaruh Komunikasi Pemasaran melalui Motivasi Konsumen pada Keputusan Pengguna Kartu Halo: Studi Kasus di Kota Padang, Sorong, dan Bandung - Nazaruddin, Erizal; Nuru, Ferdinant; Yudhakusuma, Dudi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
The purpose of this study was to analyze the effect of Company Size, Profitability, and Public Accounting Firm Size on Audit Report Lag (Empirical Study of Food and Beverage Sub-Sector Manufacturing Companies Listed on Bei in 2020-2022). This type of research is quantitative. The data used in this study were obtained from the official website of the Indonesia Stock Exchange regarding the annual report of food and beverage sub-sector manufacturing companies in 2020-2022. The data in this study are secondary data. The data collection method is the documentation method, which is done by collecting audited annual financial reports listed on the Indonesia Stock Exchange for the 2020-2022 period and available on the official website www.idx.co.id. The literature study method is carried out by analyzing journals, books, and other sources. This study uses descriptive statistical analysis methods, classical assumption tests, multiple linear regression analysis, coefficient of determination, and hypothesis testing. Hypothesis testing includes classical assumption tests as a condition of multiple linear regression. Company size has no effect on audit report lag with a t value of 0.633 and a significance of 0.528> 0.05. Profitability has a negative and significant effect on audit report lag with a t value of -2.991 and a significance of 0.003 <0.05. KAP size has a negative and significant effect on audit report lag with a t value of -3.096 and a significance of 0.002 <0.05.